MODERN ANTIPLATELET THERAPY OF ISCHEMIC HEART DISEASE PATIENTS WITH HIGH RISK OF THROMBOTIC EVENTS: DATA FROM EVIDENCE-BASED MEDICINE AND REAL PRACTICE - S. Yu. Martsevich; M. L. Ginzburg; A. M. Malysheva; Yu. N. Polyanskaya; T. G. Kheliya; N. P. Kutishenko (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study a rate of clopidogrel use in patients having indications for clopidogrel therapy according with up to date guidelines. Material and methods. Database of patients experienced acute myocardial infarction (MI) and database of patients experienced angiography because of stable ischemic heart disease (IHD) were used to evaluate clopidogrel therapy implementation. Patients with acute MI (n=84) and patients with IHD after angioplasty (n=239) were interviewed. Results. Only 14 of 84 (16.6%) patients after acute MI and 112 of 239 (47%) patients after angioplasty were taken clopidogrel within 12 months. Conclusion. The majority of patients after MI and coronary angioplasty do not receive clopidogrel despite the need of dual antiplatelet agents therapy.